MODEL PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI MAHASISWA PROGRAM STUDI PENDIDIKAN BIOLOGI FKIP UNIVERSITAS BUNG HATTA - Gusmaweti Gusmaweti (Universitas Sebelas Maret, 2014)
This study aims to improve learning outcomes by biological learning models play a role in the biology of learning in students of the Faculty of Biology Education Teaching and Education Bung Hatta University. This type of research is action research (PTK), using four stages: planning, implementation, observation and reflection. The experiment was conducted two cycles, each cycle consisting of two meetings and one-time test. Research subjects consisted of students who take courses Animal Taxonomy I semester 2013/2014 as many as 28 people. The research instrument is a matter of learning tests, observation sheets learning outcomes affective and psychomotor aspects. The results showed that the average value of learning outcomes in the cognitive aspects of the first cycle of 68.0 to 64.0% mastery learning, assessment of learning outcomes affective aspects average 73.2 and 72.9 psychomotor. In the second cycle increased cognitive learning outcomes an average of 78.1 with 79.6% completeness Study abroad. So is the affective aspect of learning outcomes increased to 77.6 and 78.6 psychomotor. The results of this study it can be concluded that the role-play learning model to improve learning outcomes of students in biology courses Animal Taxonomy I. It is suggested that teachers / lecturers are expected to use the model of learning to play a role in the material or different subjects. Keywords: models, learning, role playing and learning outcomes